The Risk of Distant Metastases in Patients With Clinical Complete Response Managed by Watch and Wait After Neoadjuvant Therapy for Rectal Cancer: The Influence of Local Regrowth in the International Watch and Wait Database. Issue 1 (21st October 2022) - Fernandez, Laura M.; São Julião, Guilherme P.; Renehan, Andrew G.; Beets, Geerard L.; Papoila, Ana L.; Vailati, Bruna B.; Bahadoer, Renu R.; Kranenbarg, Elma Meershoek-Klein; Roodvoets, Annet G. H.; Figueiredo, Nuno L.; Van De Velde, Cornelis J. H.; Habr-Gama, Angelita; et al.
Abstract : BACKGROUND: Nearly 30% of patients with rectal cancer develop local regrowth after initial clinical complete response managed by watch and wait. These patients might be at higher risk for distant metastases. OBJECTIVE: This study aimed to investigate risk factors for distant metastases using time-dependent analyses. DESIGN: Data from an international watch and wait database were retrospectively reviewed. Cox regression analysis was used to determine risk factors for worse distant metastases-free survival. Conditional survival modeling was used to investigate the impact of risk factors on the development of distant metastases. SETTING: Retrospective, multicenter database. PATIENTS: A total of 793 patients (47 institutions) with rectal cancer and clinical complete response to neoadjuvant treatment from the International Watch & Wait Database were included. MAIN OUTCOME MEASURES: Distant metastases-free survival. RESULTS: Of the 793 patients managed with watch and wait (median follow-up 55.2 mo)‚ 85 patients (10.7%) had distant metastases. Fifty-one of 85 patients (60%) had local regrowth at any time. Local regrowth was an independent factor associated with worse distant metastases-free survival in the multivariable model. Using conditional estimates, patients with local regrowth without distant metastases for 5 years (from decision to watch and wait) remained at higher risk for development of distant metastases for 1 subsequent year compared to patients without local regrowth (5-year conditional distant metastases-free survival 94.9% vs 98.4%). LIMITATIONS: Lack of information on adjuvant chemotherapy, salvage surgery for local regrowth, and heterogeneity of individual surveillance/follow-up strategies used may have affected results. CONCLUSIONS: In patients with clinical complete response managed by watch and wait, development of local regrowth at any time is a risk factor for distant metastases. The risk of distant metastases remains higher for 5 years after development of local regrowth. See Video Abstract at http://links.lww.com/DCR/C53 . EL RIESGO DE METÁSTASIS A DISTANCIA EN PACIENTES CON RESPUESTA CLÍNICA COMPLETA MANEJADA POR WATCH AND WAIT DESPUÉS DE LA TERAPIA NEOADYUVANTE PARA EL CÁNCER DE RECTO: LA INFLUENCIA DEL NUEVO CRECIMIENTO LOCAL EN LA BASE DE DATOS INTERNACIONAL WATCH AND WAIT: ANTECEDENTES: Casi el 30 % de los pacientes con cáncer de recto desarrollan un nuevo crecimiento local después de la respuesta clínica completa inicial manejada por watch and wait. Estos pacientes podrían tener un mayor riesgo de metástasis a distancia. OBJETIVO: Investigar los factores de riesgo de metástasis a distancia mediante análisis dependientes del tiempo. DISEÑO: Se revisó retrospectivamente los datos de la base de datos internacional de Watch and Wait. Se utilizó el análisis de regresión de Cox para determinar los factores de riesgo de peor sobrevida libre de metástasis a distancia. Se utilizó un modelo de sobrevida condicional para investigar el impacto de los factores de riesgo en el desarrollo de metástasis a distancia. El tiempo transcurrido hasta el evento se calculó utilizando la fecha de decisión para watch and wait y la fecha del nuevo crecimiento local para el diagnóstico de metástasis a distancia. ESCENARIO Base de datos multicéntrica retrospectiva. PACIENTES: Se incluyeron un total de 793 pacientes (47 instituciones) con cáncer de recto y respuesta clínica completa al tratamiento neoadyuvante de la base de datos internacional de Watch and Wait. PRINCIPALES MEDIDAS DE RESULTADO: Desarrollo de metástasis a distancia. RESULTADOS: De los 793 pacientes tratados con watch and wait (mediana de seguimiento de 55, 2 meses), 85 (10, 7%) tenían metástasis a distancia. 51 de 85 (60%) tuvieron recrecimiento local en algún momento. El recrecimiento local fue un factor independiente asociado a una peor supervivencia libre de metástasis a distancia en el modelo multivariable. Además, al usar estimaciones condicionales, los pacientes con recrecimiento local sin metástasis a distancia durante 5 años (desde la decisión de watch and wait) permanecieron en mayor riesgo de desarrollar metástasis a distancia durante un año subsiguiente en comparación con los pacientes sin recrecimiento local (sobrevida libre de metástasis a distancia a 5 años: recrecimiento local 94, 9% frente a no recrecimiento local 98, 4%). LIMITACIONES: La falta de información relacionada con el uso de quimioterapia adyuvante, las características específicas de la cirugía de rescate para el nuevo crecimient o local y la heterogeneidad de las estrategias individuales de vigilancia/seguimiento utilizadas pueden haber afectado los resultados observados. CONCLUSIONES: En pacientes con respuesta clínica completa manejados por Watch and Wait, el desarrollo de recrecimiento local en cualquier momento es un factor de riesgo para metástasis a distancia. El riesgo de metástasis a distancia sigue siendo mayor durante 5 años después del desarrollo de un nuevo crecimiento local. Consulte Video Resumen en http://links.lww.com/DCR/C53 . (Traducción—Dr. Felipe Bellolio )